2022
DOI: 10.1055/a-1797-7005
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Nonvigorous Neonates Born through Meconium-Stained Amniotic Fluid after a Practice Change to No Routine Endotracheal Suctioning from a Developing Country

Abstract: Objective: International Liaison Committee on Resuscitation (ILCOR) 2015 gave a weak recommendation based on low certainty of evidence against routine endotracheal (ET) suctioning in non-vigorous (NV) neonates born through meconium stained amniotic fluid (MSAF) and suggested for immediate resuscitation without direct laryngoscopy. A need for ongoing surveillance post policy change has been stressed upon. This study compared the outcomes of NV MSAF neonates before & after implementation of the ILCOR 2015 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 44 publications
(68 reference statements)
1
9
0
1
Order By: Relevance
“…Since the revised NRP guidelines in the seventh and eighth editions, several researchers have been trying to answer this controversy using data from their centers, but there are variations in the study population composition and outcomes. 22,[24][25][26][27][28][29][30]45 Similar to our study, an observational study by Chiruvolu et al 22 reported an increased incidence of NICU admissions, need for mechanical ventilation, oxygen therapy, and use of surfactant after implementing the new guidelines, while the incidence of MAS was not different in the two groups. Kalra et al 27 reviewed the California Perinatal Quality Care Collaborative database and found a decrease in the incidence or severity of MAS.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Since the revised NRP guidelines in the seventh and eighth editions, several researchers have been trying to answer this controversy using data from their centers, but there are variations in the study population composition and outcomes. 22,[24][25][26][27][28][29][30]45 Similar to our study, an observational study by Chiruvolu et al 22 reported an increased incidence of NICU admissions, need for mechanical ventilation, oxygen therapy, and use of surfactant after implementing the new guidelines, while the incidence of MAS was not different in the two groups. Kalra et al 27 reviewed the California Perinatal Quality Care Collaborative database and found a decrease in the incidence or severity of MAS.…”
Section: Discussionsupporting
confidence: 88%
“…A subsequent single-center cohort study by Kalra et al 29 on nonvigorous infants born through MSAF revealed a higher incidence of MAS (15 vs. 53%) and NICU admission for respiratory distress (18 vs. 57%). Another recent study by Kumar et al 30 showed no change in the incidence of MAS and decreased incidence of HIE in nonvigorous neonates in the no Note: Outcomes adjusted for the male gender and subsequent intubation in DR.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…При наявності задишки, яка виникає внаслідок розвитку термінального стану в плода, відбувається зміна градієнтів тиску в амніотичній рідині та дихальних шляхах і порушення опору останніх, що призводить до аспірації навколоплідних вод та їх вмісту [4,44]. Даний механізм внутрішньоутробної аспірації пояснює знижену ефективність інтратрахеального відсмоктування вмісту трахеї у новонароджених крізь навколоплідні води у випадку їх аспірації задовго до народження [20,51,52,53,54]. Вплив гіпоксії на пасаж меконію в амніотичну рідину та його подальшу внутрішньоутробну аспірацію підтверджує велика кількість раніше проведених досліджень, у яких зв'язок з гіпоксично-ішемічними явищами та САМ показує низький pH пуповинної крові та низьку оцінку за Апгар на 5-й хвилині [11,44,45,55,56].…”
Section: вступunclassified
“…Many of them were from high income countries (HICs) and aimed to evaluate the impact of this policy change on the various outcomes of NV-MSAF neonates. (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) Traditionally, meta-analyses are restricted exclusively to RCTs as the CoE derived from them are relatively higher when compared to that from observational studies. (21) Recent literature has indicated the usefulness of synthesizing data from observational studies, often termed as real-world evidence (RWE).…”
Section: Introductionmentioning
confidence: 99%